CHITOSAN: A MULTIFACET POLYMER - Patel, Dhanik Pravin; Singh, Sushma (International Journal of Current Pharmaceutical Research, 2015)
Objective: Chitosan is considerably versatile and promising biomaterial. It is a natural, tough, cationic, nontoxic, biodegradable, and biocompatible polymer obtained by alkaline deacetylation of chitin. Chitin is a polysaccharide obtained from exoskeletons of crustaceans and sea insects such as crab, krill, shrimp and crawfish etc. Besides the formerly mentioned resources it is also obtained from some fungi and bacterial cell walls. Methods: Chitosan has found wide applicability in conventional pharmaceutical devices as a potential formulation excipient, some of which include binding, disintegrating, stabilizing, suspending, tablet coating, and film forming material. Chitosan has been comprehensively investigated for its suitability for its controlled release characteristics in various studies. Chitosan presents remarkable absorption and penetration enhancing properties that makes it a good candidate for the delivery of genes and peptide. Results: It is possessing tremendous mucoadhesive and inherent anti-microbial properties, so that it can be used as a carrier for novel drug delivery. In addition to the above mentioned reasons, tailoring the controlled release and to improve the therapeutic efficacy of the low molecular weight drug compounds can also be achieved by this polymer and moreover in combination with various polymers is feasible due its compatibility i.e. low chemical reactivity. Conclusion: This brief editorial epitomizes the potential application of chitosan in the development of drug delivery systems.